Design and development of an automated product-fetching platform for electronic orders - Vlassis, Konstantinos; Papaioannou, Evi; Kaklamanis, Christos (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
We present "E-shopaholic," an innovative e-commerce platform that integrates advanced automation techniques to optimize the online shopping experience. "E-shopaholic" exploits automation to address challenges of traditional e-commerce systems, particularly in order-picking. Leveraging the Internet of Things (IoT), "E-shopaholic" employs a NodeMCU ESP8266 module and a servo motor to simulate the picking and placing of products, aiming to contribute to the evolution of efficient e-commerce operations through automation. The platform, with its real-time automated order processing and updates, aims to enhance operational efficiency by lowering order processing times, increasing accuracy, and improving the overall order fetching process. The system design and implementation are discussed in detail, highlighting the potential of IoT and automation to transform e-commerce practices. "E-shopaholic" serves as a proof of concept for scalable and cost-effective solutions in the e-commerce sector, suggesting a path forward for research and development in automated systems.